Understanding neutron capture processes in uranium deposits using combined U-Sm-Nd isotopic compositions - Quinn R. Shollenberger; Jan Render; Melissa J. Murphy; Gregory A. Brennecka (Applied Geochemistry, 2025)

Elemental and isotopic signatures of Asteroid Ryugu support three early Solar System reservoirs - Quinn R. Shollenberger; Jan Render; Josh Wimpenny; Rosalind M.G. Armytage; Nipun Gunawardena; John M. Rolison; Justin I. Simon; Gregory A. Brennecka (Earth and Planetary Science Letters, 2025)

Reassessing the proposed “CY chondrites”: Evidence for multiple meteorite types and parent bodies from Cr-Ti-H-C-N isotopes and bulk elemental compositions - Devin L. Schrader; Zachary A. Torrano; Dionysis I. Foustoukos; Conel M.O’D. Alexander; Jan Render; Gregory A. Brennecka (Geochimica et Cosmochimica Acta, 2025)

Tarda and Tagish Lake: Samples from the same outer Solar System asteroid and implications for D- and P-type asteroids - Devin L. Schrader; Edward A. Cloutis; Daniel M. Applin; Jemma Davidson; Zachary A. Torrano; Dionysis Foustoukos; Conel M. O'D. Alexander; Kenneth J. Domanik; Moe Matsuoka; Tomoki Nakamura; Thomas J. Zega; Gregory A. Brennecka; et al. (Geochimica et Cosmochimica Acta, 2024)

A common isotopic reservoir for amoeboid olivine aggregates (AOAs) and calcium-aluminum-rich inclusions (CAIs) revealed by Ti and Cr isotopic compositions - Zachary A. Torrano; Conel M.O'D. Alexander; Richard W. Carlson; Jan Render; Gregory A. Brennecka; Emma S. Bullock (Earth and Planetary Science Letters, 2024)

Gallium isotopic constraints for the origin of the Earth-Moon system - Jan Render; Josh Wimpenny; Lars Borg (Earth and Planetary Science Letters, 2023)

Long-term serological follow-up after primary Coxiella burnetii infection in patients with vascular risk factors for chronic Q fever - Sheila B. Buijs; Sanne K. Stuart; Jan Jelrik Oosterheert; Steffi Karhof; Andy I. M. Hoepelman; Nicole H. M. Renders; André S. van Petersen; Chantal P. Bleeker-Rovers; Peter C. Wever; Olivier H. J. Koning (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
We evaluated the long-term serological follow-up of patients with vascular risk factors for chronic Q fever that were previously C oxiella burnetii seropositive. C. burnetii phase I IgG titers were reevaluated in patients that gave informed consent or retrospectively collected in patients already deceased or lost to follow-up. Of 107 patients, 25 (23.4%) became seronegative, 77 (72.0%) retained a profile of past resolved Q fever infection, and five (4.7%) developed chronic Q fever. We urge clinicians to stay vigilant for chronic Q fever beyond two years after primary infection and perform serological testing based on clinical presentation.